Left ventricular noncompaction: Clinical-echocardiographic study - Nikolić Aleksandra; Jovović Ljiljana; Tomić Slobodan; Vuković Milan (Vojnosanitetski Pregled)
Background/Aim. Left ventricular noncompaction (LVNC) is a disorder in endomyocardial morphogenesis, seen either isolated (in the absence of other cardiac anomalies) or in association with congenital heart disease and some neuromuscular diseases. Intrauterine arrest of the compaction of myocardial fibers is postulated to be the reason of LVNC. Recognition of this condition is extremely important due to its high mortality and morbidity that lead to progressive heart failure, ventricular arrhythmias and thromboembolic events. The aim of this study was to determine the prevalence and clinical presentation of LVNC among consecutive outpatients according to clinical and echocardiographyic findings. Methode. A total of 3,854 consecutive patients examined at the Institute for Cardiovascular Diseases within a period January 2006 - January 2007 were included in the study. All the patients underwent echocardiographic examination using the same equipment (Vivid 7, GE Medical System). Echocardiographic parameters and clinical presentation in patients with echocardiographic criteria for LVNC were analyzed. Results. Analyzing 3,854 consecutive outpatients, using two-dimensional Color Doppler echocardiography from January 2006 to January 2007, 12 patients met the criteria for LVNC. Seven of them were male. The mean age at diagnosis was 45 ± 15 years. Analyzing clinical manifestation of LVNC it was found that seven patients had signs of heart failure, six had arrhythmias with no embolic events. Conclusion. Our results suggest that the real prevalence of LVNC may be higher than expected. New studies have to be done to solve this problem.